The relationship between organizational commitments, person-fit, organizational culture and withdrawal behaviors / Fatin Nadzirah Hasan - Hasan, Fatin Nadzirah (2014)
This study to estimate the possibility organizational commitment (OC), personorganization fit (P-O fit); person-reform fit (P-R fit) and organizational culture can influence employee withdrawal behaviors and age as moderator. A survey was sent to 200 employees at Taiyo Technology (M) Sdn. Bhd. Participation in the study was convenience. The participants were 200 working adults. All data had been analyzed using social package for social science. This paper provides several interesting findings. While no relationship was found between organizational commitments (OC) and personorganization fit (P-O Fit) with withdrawal behavior. There is relationship between new variables person-reform fit (P-R Fit) and organizational culture with withdrawal behavior. Besides, there is one significant relationship between organizational commitment with withdrawal behavior when age act as moderator. Results are discussed.